L-arginine, a nitric oxide precursor, reduces dapsone-induced methemoglobinemia in rats - Natália Valadares de Moraes; Mateus Machado Bergamaschi; Maria de Lourdes Pires Bianchi; Juliana Bordinassi Bragheto; Wilson Roberto Malfará; Regina Helena Costa Queiroz (Universidade de São Paulo, 2012)
Dapsone use is frequently associated to hematological side effects such as methemoglobinemia and hemolytic anemia, which are related to N-hydroxylation mediated by the P450 enzyme system. The aim of the present study was to evaluate the influence of L-arginine supplementation, a precursor for the synthesis of nitric oxide, as single or multiple dose regimens on dapsone-induced methemoglobinemia. Male Wistar rats were treated with L-arginine at 5, 15, 30, 60 and 180 mg/kg doses (p.o., gavage) in single or multiple dose regimens 2 hours prior to dapsone administration (40 mg/kg, i.p.). The effect of the nitric oxide synthase inhibitor L-NAME was investigated by treatment with multiple doses of 30 mg/kg (p.o., gavage) 2 hours before dapsone administration. Blood samples were collected 2 hours after dapsone administration. Erythrocytic methemoglobin levels were assayed by spectrophotometry. The results showed that multiple dose supplementations with 5 and 15 mg/kg L-arginine reduced dapsone-induced methemoglobin levels. This effect is mediated by nitric oxide formation, since the reduction in methemoglobin levels by L-arginine is blocked by simultaneous administration with L-NAME, a nitric oxide synthase inhibitor. O uso da dapsona é frequentemente associado a efeitos adversos hematológicos, como a metemoglobinemia e anemia hemolítica, ambos relacionados com a N-hidroxilação mediada pelo sistema P450. O objetivo do estudo foi avaliar a influência da suplementação de L-arginina, um precursor da síntese de óxido nítrico, administrado em regime de dose única ou múltipla na metemoglobinemia induzida pela dapsona. Ratos machos Wistar foram tratados com L-arginina (po, gavagem) em dose única ou múltipla de 5, 15, 30, 60 e 180 mg/kg 2 horas antes da administração de dapsona (40 mg/kg, ip). O efeito do L-NAME, um inibidor de óxido nítrico sintase (NOS), foi avaliado através do tratamento com doses múltiplas de 30 mg/kg. Amostras de sangue foram coletadas duas horas após a administração de dapsona. A concentração de metemoglobina eritrocitária foi analisada por espectrofotometria. Os resultados mostraram que a suplementação em dose múltipla de 5 e 15 mg/kg de L-arginina reduziu os níveis de metemoglobina induzida pela dapsona. Este efeito é mediado pela formação de óxido nítrico, uma vez que a redução nos níveis de metemoglobina pela L-arginina é bloqueada pela administração simultânea de L-NAME, um inibidor da óxido nítrico sintase.